THE CONTENT OF THE DEVELOPMENT OF INFORMATION COMPETENCE OF FUTURE EDUCATORS - M. A. Yakubova (Web of Journals Publishing, 2024)
This article talked about the content of the development of information competence of future educators.
Keywords: digitization of Education, Information and Communication Technology, Computer literacy, information and technological training, modern education, educational system, professional activities, tools, skillful use, ability.